The influence effect of regional carbon emission reduction under the perspective of fiscal decentralization: Government intervention or market mechanism? - Li, Chuang; Li, Keke; Wang, Liping (Managerial and decision economics, 2024)
Based on the perspective of fiscal decentralization, the study focuses on 30 provinces in China and employs various econometric models including the threshold model, spatial econometric model, mediation model, and regulation model. The research findings indicate that fiscal decentralization has a double‐threshold effect on government intervention, market mechanisms, and regional carbon emission reduction. Both government intervention and market mechanisms have inhibiting effects on carbon emission, with significant coefficients of GOVI and MARM at the 1% level. The cooperation between government intervention and the market mechanism effectively limits carbon emissions. Government intervention facilitates regional carbon emission reduction through the construction of new infrastructures and energy structure transformation, yielding a significant intermediary effect. The market mechanism is positively regulated through green finance and technology innovation to promote regional carbon emission reduction. Moreover, government intervention enables the market to achieve carbon emission reduction more effectively, especially in areas with a higher degree of government intervention. Continuous improvement and upgrading of regional and national carbon markets are essential to attain the carbon peak and carbon neutrality goals. Furthermore, attracting more participants to these markets for emission control subjects is necessary to enhance the effectiveness of government–market coordination.